2011
DOI: 10.1016/j.jcps.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Building trust to increase purchase intentions: The signaling impact of low pricing policies

Abstract: We examine the differential signaling impact of two low pricing policies, Price Matching Guarantees and Everyday Low Prices, on consumers' trusting beliefs and purchase intentions. We demonstrate that both PMG and EDLP pricing policies signal stores' ability to offer lower prices. However, whether these sellers were perceived as benevolent, and-consequently-consumers' purchase intentions, varied critically depending upon price uncertainty. Perceived benevolence and purchase intentions were significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In this regard, Grewal et al (2004) supported the relationship among perception of trust, price fairness and repurchase intentions and revealed that consumers view larger price difference as more unfair. Similarly, White and Yuan (2011) and Kim et al (2012)…”
Section: Trusting Beliefs and Uncertainty Avoidancementioning
confidence: 98%
“…In this regard, Grewal et al (2004) supported the relationship among perception of trust, price fairness and repurchase intentions and revealed that consumers view larger price difference as more unfair. Similarly, White and Yuan (2011) and Kim et al (2012)…”
Section: Trusting Beliefs and Uncertainty Avoidancementioning
confidence: 98%
“…Consumer trust can potentially explain the effectiveness of different marketing strategies on consumer behavior. For instance, low-price policies increase consumers’ trust in sellers’ ability, which in turn enhances consumers’ purchase intention (White and Yuan 2012). Similarly, a firm’s investments in website design enhance consumers’ trust in the firms’ abilities, which increases consumers’ online purchase intention (Schlosser, White, and Lloyd 2006).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In addition, Hsiao et al (2010) and White and Yuan (2011) revealed perceived ability and perceived benevolence as important antecedents of trust and examined the impact of low pricing policies on only two components of trusting beliefs, i.e., ability and benevolence, thus ignored competency of an e-vendor and other factors like reputation of a firm, which are of a great concern while analysing intentions. In the same context, Kim et al (2012) investigated the impact of only price and trust on consumer purchase decision, but failed to include other important constructs like image of e-vendor, their benevolent character, integrity, etc.…”
Section: Introductionmentioning
confidence: 99%